Comparing Health and safety sentencing in NZ and abroad - Lill, Joseph (New Zealand Journal of Health and Safety Practice, 2024)
A review of aspects of the sentencing regime in New Zealand with a focu on financial capacity and alternative orders. It highlights the different maximum penalty and approach to settng fine levels in England & Wales as well as literature from Australia regarding the need for regulators and courts to engage with alternative orders.